Experimental Methods and Nonlinear Optical Properties of Open-Shell Molecular Species - Kenji Kamada (Chemistry, 2025)
Degenerate third-order nonlinear optical (NLO) responses of organic molecules have a wide range of applications in science and engineering because they relate to the intensity-dependent refractive index (IDRI) and nonlinear absorption (NLA), such as two-photon absorption (TPA). Among the many molecular systems, open-shell molecular species such as intermediate singlet diradicaloids have attracted considerable attention because of their enhanced response, predicted theoretically by Nakano et al. Experimental studies for proofing and evaluating the enhanced nonlinearities play an important role in the development of the field. This tutorial review provides the solid fundamentals of the NLO processes of open-shell molecular species even to those who are not familiar with the experimental works. Its scope ranges from the basics of NLO responses, definitions, and interrelations of the key parameters of the responses, such as hyperpolarizability and TPA cross-section, to the experimental techniques used to evaluate them. Including the recent achievements, the evolution of experimental works on the TPA properties of singlet diradicaloids is also reviewed according to families of molecular structures.